Core photographs of the Rotliegend reservoir of the Groningen gas field and surrounding areas - Visser, Clemens A.; Bokhorst, Karel (Utrecht University, 2022)
The Groningen gas field is the largest gas field in Europe and has been showing seismicity since the 1990s. The ~200 meter deep gas reservoir is situated at ~3 km depth, and comprises Permian (Slochteren) sandstone from the Rotliegend formation. The reservoir has been cored extensively by the field operator, the Nederlandse Aardolie Maatschappij (NAM). This dataset constitutes photographs of core slabs (core-parallel slices) taken from the reservoir intervals of 67 cored wells in the Groningen field and surrounding areas. It allows for detailed inspection of sedimentological features of the Rotliegend reservoir of the Groningen Field. The core photographs are provided by NAM, open access. Contact person: Clemens Visser - NAM - clemens.visser@shell.com
Keywords: Natural Sciences - Earth and related environmental sciences (1.5); Groningen gas field; Rotliegend sandstone; Slochteren sandstone; Core photographs; Sedimentological features; Petrology; Seismicity; Compaction; Subsidence; Core slab; NAM; EPOS-NL